Diagnosis and subclassification of lymphomas and non‐neoplastic lesions involving mediastinal lymph nodes using endobronchial ultrasound‐guided transbronchial needle aspiration. Issue 12 (31st May 2011) - Ko, Hyang Mi; da Cunha Santos, Gilda; Darling, Gail; Pierre, Andrew; Yasufuku, Kazuhiro; Boerner, Scott L.; Geddie, William R.
<x xml:space="preserve">Abstract</x> Introduction: The value of endobronchial ultrasound‐guided transbronchial needle aspiration (EBUS‐TBNA) has been established for staging mediastinal lymph nodes in lung carcinoma patients with radiologically enlarged lymph nodes, but its utility for evaluation of primary lymph node disorders is not well defined. The objective of this study was to evaluate the usefulness of EBUS‐TBNA with on‐site assessment and triage of sample for multiple ancillary techniques, for the diagnosis and subclassification of lymphomas and non‐neoplastic lesions involving mediastinal lymph nodes. Methods: One hundred and twenty consecutive patients who underwent EBUS‐TBNA between January 2008 and August 2009 were reviewed. The final cytological diagnosis was based on air‐dried Romanowsky and alcohol‐fixed Papanicolaou stained direct smears, immunohistochemistry, immunophenotyping, and fluorescence in situ hybridization (FISH). Results: A total of 38 cases were included in this study consisting of eight reactive lymphoid hyperplasia, 20 granulomatous lymphadenitis (17 non‐necrotizing and 3 necrotizing granulomatous inflammations), 3 Hodgkin lymphomas and 7 non‐Hodgkin lymphomas (1 small lymphocytic lymphoma (SLL), 1 SLL with scattered Reed‐Sternberg cells, 1 marginal zone lymphoma, and 4 large B cell lymphomas). Cultures performed in 13 cases were negative for AFB and fungi. Immunophenotyping and immunohistochemistry for MIB1 in six cases, and FISH in five cases provided necessary information for subclassification. Conclusions: EBUS‐TBNA is a minimally invasive procedure which provides sufficient sample for definitive primary diagnosis and classification of malignant lymphoma and granulomatous inflammation in patients with mediastinal lymphadenopathy. Rapid on‐site specimen assessment is invaluable for appropriate assignment of sample to ancillary studies. Diagn. Cytopathol. 2013;41:1023–1030. © 2011 Wiley Periodicals, Inc.